Cytoreductive Surgery With Hyperthermic Intraperitoneal Chemotherapy for the Treatment of Recurrent Endometrial Carcinoma Confined to the Peritoneal Cavity. Issue 5 (1st June 2010) - Bakrin, Naoual; Cotte, Eddy; Sayag-Beaujard, Anne; Raudrant, Daniel; Isaac, Sylvie; Mohamed, Faheez; Gilly, François-Noel; Glehen, Olivier
Abstract : Our objective was to determine if cytoreductive surgery (CRS) with hyperthermic intraperitoneal chemotherapy (HIPEC) is a feasible therapeutic option for treatment of peritoneal recurrence of endometrial carcinoma. Between August 2002 and May 2007, 5 patients with recurrent endometrial carcinoma confined to the peritoneal cavity who underwent CRS with HIPEC. Cisplatin (1 mg/kg) and mitomycin C (0.7 mg/kg) were perfused at an inflow temperature of 46 to 48°C for 90 minutes under systemic hypothermia (32°C). Of the 5 patients treated, histopathological type and International Federation of Gynecology and Obstetrics stage were as follows: IB endometrioid (n = 1), IIIA endometrioid (n = 1), IIIC endometrioid (n = 2), and IC endometrioid + pseudosarcomatoid component (n = 1). The mean interval from initial surgery to CRS with HIPEC was 47.5 months (10-120 months). In all patients, CRS was complete. One patient with pseudosarcomatoid component developed recurrent disease 10 months after surgery and died 2 months later. One patient experienced early recurrence with a malignant pleural effusion and died. Three patients are alive and disease free at 7, 23, and 39 months from surgery with good performance status. Regarding the toxicity of the procedure, highly selected patients with recurrent endometrial carcinoma confined to the peritoneal cavity may benefit from improved survival after CRS with HIPEC.